Neuromatch Academy: Teaching Computational Neuroscience with Global Accessibility. Issue 7 (July 2021) - ,; van Viegen, Tara; Akrami, Athena; Bonnen, Kathryn; DeWitt, Eric; Hyafil, Alexandre; Ledmyr, Helena; Lindsay, Grace W.; Mineault, Patrick; Murray, John D.; Pitkow, Xaq; Puce, Aina; et al.
Abstract : Neuromatch Academy (NMA) designed and ran a fully online 3-week Computational Neuroscience Summer School for 1757 students with 191 teaching assistants (TAs) working in virtual inverted (or flipped) classrooms and on small group projects. Fourteen languages, active community management, and low cost allowed for an unprecedented level of inclusivity and universal accessibility.